Interleukin-22 induces hepatic stellate cell senescence and restricts liver fibrosis in mice - Kong, Xiaoni; Feng, Dechun; Wang, Hua; Hong, Feng; Bertola, Adeline; Wang, Fu-Sheng; Gao, Bin (Hepatology (Baltimore, Md.), 2012)
Interleukin (IL)‐22 is known to play a key role in promoting antimicrobial immunity, inflammation, and tissue repair at barrier surfaces by binding to the receptors, IL‐10R2 and IL‐22R1. IL‐22R1 is generally thought to be expressed exclusively in epithelial cells. In this study, we identified high levels of IL‐10R2 and IL‐22R1 expression on hepatic stellate cells (HSCs), the predominant cell type involved in liver fibrogenesis in response to liver damage. In vitro treatment with IL‐22 induced the activation of signal transducer and activator of transcription (STAT) 3 in primary mouse and human HSCs. IL‐22 administration prevented HSC apoptosis in vitro and in vivo, but surprisingly, the overexpression of IL‐22 by either gene targeting (e.g., IL‐22 transgenic mice) or exogenous administration of adenovirus expressing IL‐22 reduced liver fibrosis and accelerated the resolution of liver fibrosis during recovery. Furthermore, IL‐22 overexpression or treatment increased the number of senescence‐associated beta‐galactosidase‐positive HSCs and decreased alpha‐smooth muscle actin expression in fibrotic livers in vivo and cultured HSCs in vitro. Deletion of STAT3 prevented IL‐22‐induced HSC senescence in vitro, whereas the overexpression of a constitutively activated form of STAT3 promoted HSC senescence through p53‐ and p21‐dependent pathways. Finally, IL‐22 treatment up‐regulated the suppressor of cytokine signaling (SOCS) 3 expression in HSCs. Immunoprecipitation analyses revealed that SOCS3 bound p53 and subsequently increased the expression of p53 and its target genes, contributing to IL‐22‐mediated HSC senescence. Conclusion: IL‐22 induces the senescence of HSCs, which express both IL‐10R2 and IL‐22R1, thereby ameliorating liver fibrogenesis. The antifibrotic effect of IL‐22 is likely mediated by the induction of HSC senescence, in addition to the previously discovered hepatoprotective functions of IL‐22. (HEPATOLOGY 2012;56:1150–1159)